The Frontier Tribal Belt : Genesis and Purpose Under the Raj - Salman Bangash (Karachi Oxford University Press, 2016)
This book deals with one of the most complicated frontier quandaries ever faced by the British Empire in India, as the British Raj attempted either to control or accommodate the Pakhtuns of the North West Frontier, because the British colonial interest clashed with the centuries-old tribal formation. The Tribal Belt was one of the most ungovernable, perilous, and hazardous regions among the British Empires many frontiers spread across the globe. For centuries, the tribes defied all those who wanted to extricate and dislodge them from their strategic position straddling the natural gateways leading from Turkistan (Central Asia) into the Indian subcontinent. For the British, tribal structure and organization, and their socio-political and religious dynamics, were something quite new, challenging, and exigent. The tribes that populated the area were left outside the British administrative structures of settled India, and instead ruled them with a peculiar and unprecedented tribal administrative structure which fulfilled their imperial interests. The book discusses in detail the political, administrative, and social intricacies of the Tribal belt under British rule.
Include Maps, Illustrations, Bibliography, Glossaries and Index.
Genesis and Purpose Under the Raj.
Keywords: India -- British Occupation of India (1765-1947) -- Borderlands -- Pakistan--Federally Administered Tribal Areas